2015
DOI: 10.1007/s00122-015-2474-4
|View full text |Cite
|
Sign up to set email alerts
|

QTL for seed protein and amino acids in the Benning × Danbaekkong soybean population

Abstract: We identified QTL associated with protein and amino acids in a soybean mapping population that was grown in five environments. These QTL could be used in MAS to improve these traits. Soybean, rather than nitrogen-containing forages, is the primary source of quality protein in feed formulations for domestic swine, poultry, and dairy industries. As a sole dietary source of protein, soybean is deficient in the amino acids lysine (Lys), threonine (Thr), methionine (Met), and cysteine (Cys). Increasing these amino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
174
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(207 citation statements)
references
References 50 publications
20
174
3
Order By: Relevance
“…Despite this limitation, the evaluation of crude protein in legume seeds has proven to be effective in germplasm evaluation, and breeding and genetics studies pertaining to protein content. In soybean, thanks to such a methodology, Warrington et al [21] reported 4 QTLs associated with crude protein. Similarly, Jadhav et al [22] identified 4…”
Section: Resultsmentioning
confidence: 99%
“…Despite this limitation, the evaluation of crude protein in legume seeds has proven to be effective in germplasm evaluation, and breeding and genetics studies pertaining to protein content. In soybean, thanks to such a methodology, Warrington et al [21] reported 4 QTLs associated with crude protein. Similarly, Jadhav et al [22] identified 4…”
Section: Resultsmentioning
confidence: 99%
“…Soybeans [ Glycine max (L.) Merrill ] contain complete protein and oil, providing all the essential amino acids necessary for the human diet [1]. Hence, a great effort has been made to increase soybean yield, while maintaining a high level of quality characteristics [2].…”
Section: Introductionmentioning
confidence: 99%
“…Both human and animal consumption of soybean is predicted to increase as the demand for plant and animal protein as well as the world population grows [5]. About 77% of animal meal consumption is dependent on soybean meal, used as a source of protein and specific amino acids.…”
Section: Introductionmentioning
confidence: 99%